2000
DOI: 10.1063/1.372145
|View full text |Cite
|
Sign up to set email alerts
|

Nd 3+ -doped fluoroaluminate glasses for a 1.3 μm amplifier

Abstract: A Nd3+-doped 1.3 μm fiber amplifier has the potential to be an efficient, high-gain device. A major problem to overcome is the long wavelength of the gain spectrum. In the majority of Nd3+-doped glasses the gain is shifted out of the second telecom window as a result of long-wavelength emission and signal excited-state absorption (ESA). In this article we present new fluoroaluminate glasses developed as hosts for the 1.3 μm Nd3+-doped fiber amplifier. Nd3+ emission peaks below 1320 nm were demonstrated in bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…The large spectral overlap between Yb 3+ emission and Er 3+ absorption result in an efficient Yb 3+ → Er 3+ energy transfer in Er 3+ -Yb 3+ codoped materials. One of the interesting RE ions is Nd 3+ , whose lasing and light amplification in the glass hosts has been known since many years [6,7]. Neodymiumglass lasers are employed to produce ignition in nuclear fusion research; high-power lasers have found numerous applications in materials processing, and femtosecond mode-locked lasers have recently become commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…The large spectral overlap between Yb 3+ emission and Er 3+ absorption result in an efficient Yb 3+ → Er 3+ energy transfer in Er 3+ -Yb 3+ codoped materials. One of the interesting RE ions is Nd 3+ , whose lasing and light amplification in the glass hosts has been known since many years [6,7]. Neodymiumglass lasers are employed to produce ignition in nuclear fusion research; high-power lasers have found numerous applications in materials processing, and femtosecond mode-locked lasers have recently become commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…They shift in wavelength when the rare earth is doped into the glass host because of the "nephlauxetic" effect. 27,28 This happens when the electronic orbitals within the 4f configuration are deformed in the presence of the host ligand field. With the increase in the overlap of the oxygen orbitals and the 4f orbitals, the energy level structure of the Nd 3+ ion contracts, leading to the wavelength shift.…”
Section: Optical Absorption and Fluorescence Measurementsmentioning
confidence: 99%
“…The 4f-4f electronic transitions of rare earth ions play an important role in the application such as optical fiber amplifiers, solid-state lasers, planar waveguides and compact microchip lasers (9)(10)(11). In the visible region, the Dy 3+ ion emits intense yellow (570-600 nm) and blue (470-500 nm) luminescence corresponding to the 4 F 9/2 → 6 H 13/2 and 4 F 9/2 → 6 H 15/2 transitions, respectively.…”
Section: Introductionmentioning
confidence: 99%